Translocation of N-acetyl Cysteine Capped Fluorescent Quantum Dots in Plant Tissue: Confocal Imaging Studies. Issue 1754 (8th April 2015) - Das, Smruti; Tharkur, Jeremy; Tetard, Laurene; Santra, Swadeshmukul
ABSTRACT: Semiconductor fluorescent quantum dots (Qdots) are popularly used as bioimaging taggants in live cell imaging and spectroscopy. In recent years, Qdots taggants are emerging in agricultural applications. Studies are primarily focused on nanotoxicity of ultra-small size water-soluble Qdots in plant systems. Nanotoxicity is correlated with Qdot core composition and surface coating. However, Qdots with certain chemical composition and surface coating may boost plant growth. In this study, we report that N-acetyl cysteine (NAC) capped ∼3.5 nm size ZnS:Mn/ZnS Qdots (NAC-Qdot) are efficiently uptaken by the snow pea ( Pisum sativum L., a model plant ) vascular system, enhancing the root growth at a dose level of 80 μg/mL. Fluorescence microscopy studies confirmed localization of NAC-Qdots in the intercellular regions. Germination and growth of the snow pea seeds were found to be strongly dependent on Qdot dosage and incubation time with Qdots. Seed germination reached 100% within 48 hours of NAC-Qdot exposure. Based on our preliminary findings, it is suggested that NAC-Qdot can be used as systemic plant nutrient material for boosting the seed germination and plant growth.